Application of Waterfall model in development of family planning participants information system - Al Fajar, Mulya; Dar, Muhammad Halmi; Rohani, Rohani (Politeknik Ganesha Medan, 2022)
The purpose of the family planning program is to improve the welfare of mothers and children, which is the basis for the realization of a prosperous society by controlling birth control as well as controlling population growth. The Department of Population Control and Family Planning in Labuhanbatu Regency has the task of carrying out family planning programs in the Labuhanbatu Regency area whose implementation is assisted by Family Planning Extension Officers in 9 existing sub-districts. District officers record and report family planning data in each sub-district every month. Recording and reporting of family planning data is still done manually. This manual system resulted in the process of submitting reports being delayed due to distance problems between sub-districts and districts. The delay in submitting this report has an impact on the performance of the institution itself. This study aims to overcome these problems with the solution of making a web-based family planning participant data collection information system. The system development method used is the Waterfall model. From the results of the implementation and testing of the system, it is found that the Codeigniter framework can be implemented in a family planning participant data collection information system quickly and easily. Tests using the Blackbox testing method also show valid results. From the results of this study, it can be concluded that to apply the waterfall method in designing and developing a KB participant data information system in Labuhanbatu Regency, it must go through five stages, namely, analyzing system requirements, designing systems using UML, implementing systems with a codeigniter framework, conducting trials with blackbox testing methods, and perform system maintenance. With this system, it is hoped that it can become a recommendation and reference for the Labuhanbatu Regency Population Control and Family Planning Service to implement it so that the problem of delays in reporting family planning data can be handled properly.